2016
DOI: 10.1016/j.asr.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid rotation and orbit control via laser ablation

Abstract: This paper presents an approach to control the rotational motion of an asteroid while a spacecraft is deflecting its trajectory through laser ablation. During the deflection, the proximity motion of the spacecraft is coupled with the orbital and rotational motion of the asteroid. The combination of the deflection acceleration, solar radiation pressure, gravity field and plume impingement will force the spacecraft to drift away from the asteroid. In turn, a variation of the motion of the spacecraft produces a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Even more challenging is to navigate a formation of spacecraft, particularly with heterogeneous sensors. Recent work by one of the authors demonstrated the possibility to autonomously navigate a formation of spacecraft around an asteroid with a distributed fault-tolerant autonomous system [1] [2]. The complexity increases even further in the case of a binary system due the interaction between the primary and the secondary asteroid.…”
Section: Introductionmentioning
confidence: 99%
“…Even more challenging is to navigate a formation of spacecraft, particularly with heterogeneous sensors. Recent work by one of the authors demonstrated the possibility to autonomously navigate a formation of spacecraft around an asteroid with a distributed fault-tolerant autonomous system [1] [2]. The complexity increases even further in the case of a binary system due the interaction between the primary and the secondary asteroid.…”
Section: Introductionmentioning
confidence: 99%
“…Independently from the chosen technique, a common problem is represented by the fact that big space items could be tumbling at a relatively high rate at the time the deflection is imparted. In this paper we tackle this detumbling problem by using a laser ablation method, considering the former study of [2], where a laser was used to deflect an asteroid while decreasing its angular velocity. In fact, as it will be shown in Section 2, it is necessary to reduce the angular rate because of the effectiveness of this method is affected by the local surface velocity.…”
Section: Introductionmentioning
confidence: 99%
“…This task will be achieved by using a monocular camera and a distance sensor (such as a LIDAR), with no prior knowledge either of the relative pose or of the target's shape. Such a target is clearly more difficult to analyze with respect to the asteroid dealt in [14,15], as its dynamics can be far more complex and fast. The addition of the target's shape reconstruction, not tackled in [16], is significant with respect to inspection tasks and to the need to evaluate target's inertia characteristics and possible locations for a possible grasp or dock.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Mathies [14] applied the two-view motion algorithm to a landing maneuver on a small body and made use of an altimeter to compute the scale variation between two images during the descent. Vetrisano et al [15] studied the use of cameras and intersatellite links between a swarm of spacecraft during the rendezvous to an asteroid, to estimate both the relative state and the relative angular velocity of the body. Oumer and Panin [16] presented a camera-based 3D feature tracking method used to estimate the position and velocities of an observed rigid body without reconstructing its shape.…”
Section: Introductionmentioning
confidence: 99%